University students’ perceptions on Corporate Internet Financial Reporting:Evidence from Sri Lanka - Sarifudeen, Ahamed Lebbe; Wanniarachchi, C. M. (The journal of contemporary issues in business and government, 2021)
The study investigates empirically the perceptions of users of financial statements (especially university students) on the various aspects of Internet Financial Reporting (IFR). Further, this study examines the factors that influence companies in Sri Lanka to engage in IFR. The advantages and disadvantages of using this new technology for financial reporting were also discussed. Users’ perceptions on financial statements were sought using a survey mailed questionnaire. The findings of this study suggested six main factors that companies to engage in IFR: Enhancingthe corporate image, companies in line with the development of technology, competition in the industry, stabilizing and enhancing share prices, receiving government support, and societal responsibility.The findings also revealed three factors that inhibit firms from engaging in IFR: required expertise from the company, need to keep the information updated to be of use, and concern over information security. Another significant result revealed increased information and analysis, navigational ease, global reach, and mass communication as the three most important advantages of financial reporting on the internet.Moreover, security problems are the disadvantages of placing financial information on the internet. The evidence on Sri Lanka is relevant to other emerging capital markets. Finally, This study provides the knowledge gap in user’s perceptions of IFR and also it is expected to have significant policy implications.